Design of WEB Based Information System for Correspondence and Community Complaint Services [Perancangan Sistem Informasi Layanan Surat Menyurat dan Pengaduan Masyarakat Berbasis WEB] - Dwi Cahyono, Qitfirul; Eviyanti, Ade; Intan Mauliana, Metatia; Findawati, Yulian (Indonesian Journal Publisher, 2024)
Public services are very important for the government to see how much success it has in carrying out services to the community. Correspondence is very important in a village government, because it is a separate necessity for the community in managing files and also complaints which are activities that can help in realizing prosperity in a village. In this study the authors developed an information system to assist the community in managing letters to the government and making complaints so that the community does not need to come to the village government office. The author uses the CodeIgniter framework, the PHP programming language and the MySQL database in designing a correspondence information system. To carry out work on this article using the waterfall method because this method has structured stages in the design of this information system. This method begins with a needs analysis, system design, implementation, testing, maintenance.The result obtained in the user acceptance test get a total percentage of 73%.